Sinkretisme Pemujaan Hindu Konghucu di Pura Penyagjagan Kabupaten Bangli - I Made Pasek Subawa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Syncretism puts the fusion of two religious teachings/beliefs into one unit which makes it have its own peculiarities. This idea shows that the syncriticalism of Hindu-Confucian beliefs found in the Penyagjagan Temple of Bangli Regency is a long history of trade relations or other expansions between Balinese (Hindu) and Chinese (Confucian) which are inherited in the system of worship and social relations. Penyagjagan Temple as a Hindu-Confucian union as a sign that two different teachings can merge in the temple environment (mandala). The union is not only in temples with Hindu and Confucian nuances, but also in the system of worship (mantra) and upakara means. This makes syncretism give birth to a religious identity as a symbolic that characterizes the peculiarities of the religious and cultural system of the Hindu-Confucian community that worships the Penyagjagan Temple.